2014
DOI: 10.4172/2329-891x.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infections and Related Risk Factors among Street Dwellers in Addis Ababa, Ethiopia

Abstract: Background: Epidemiological information on the prevalence of various intestinal parasitic infections in different sectors of the society and localities is very important to develop appropriate control strategies. Many studies have been conducted to determine the prevalence of intestinal parasitic infections in Ethiopia. However, studies pertaining to the prevalence of intestinal parasitic infections among the street dwellers are limited. Therefore, the aim of this study was to determine the prevalence of intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
28
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 19 publications
15
28
4
Order By: Relevance
“…The risk factors of strongyloidiasis increased with illiteracy OR= 2.923(95% CI 1.096-7.793, P= 0.032) which is similar to the finding of [32] in Ethiopia. The climatic factor such as rainy season OR= 3.424(95% CI 1.183-9.905, P= 0.023) associated with infection than other season.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The risk factors of strongyloidiasis increased with illiteracy OR= 2.923(95% CI 1.096-7.793, P= 0.032) which is similar to the finding of [32] in Ethiopia. The climatic factor such as rainy season OR= 3.424(95% CI 1.183-9.905, P= 0.023) associated with infection than other season.…”
Section: Discussionsupporting
confidence: 82%
“…This is the first time study on Strongyloidiases in tea garden community of Sylhet and there is paucity of information about it. The present study showed female (13.82%) participants have higher prevalence of S. stercoralis infection than male (11.86%) which is also supported by [32]. The winter season disclosed highest percentage of infection whereas rainy stood second and summer stood lowest infection.…”
Section: Risk Factor Assessment For S Stercoralis Infectionsupporting
confidence: 84%
“…The predominanat parasite in this study was A.lumbricoides with a prevalence of (11.4%), which was lower than reports in Addis Ababa, Chencha, Zegie and Azezowhich found magnitudes of 34.9%, 60.5%, 18.4%, 28.8% (20)(21)(22)26), respectively. This might be due to differences in age.…”
Section: Prevalence and Associated Risk Factors Of Intestinal Parasitcontrasting
confidence: 79%
“…Participants with swimming habits in the river were two times (COR, 2.283, 95% CI 1.146-4.549) more positive for intestinal parasitic infection than their counter parts. (Table 3) ANRS and Azezo Atse Fasil primary school respectively (5,17,18,(20)(21)(22)(23)(24)(25)(26). The nding was comparable with that of a study conducted in Babile town 13.8% (27) but higher than of a study conducted in Ghana and noted 15% (28).…”
Section: Prevalence and Associated Risk Factors Of Intestinal Parasitmentioning
confidence: 99%
“…Female showed higher prevalence of Strongyloides infection than male (Mekonnen et al, 2014;Vonghachack et al, 2015). The elderly persons had higher prevalence than the young participants in Cambodia .…”
Section: Risk Factors Host Factorsmentioning
confidence: 92%